Water-Agriculture-Energy Nexus in Central Asia through the Lens of Climate Change - Umirbekov, Atabek; Akhmetov, Almaz; Gafurov, Zafar (2023)
This study examines the climate vulnerabilities of Central Asia's water, agriculture, and energy sectors at province level, using an index-based approach that quantifies their exposure, sensitivities, and adaptive capacities. As a climate exposure metric for the water and agriculture sectors the study uses projections of river discharge and agricultural productivity under RCP 2.6 and RCP 8.5, which are viewed here as 'optimistic' and 'pessimistic' climate scenarios respectively. The sensitivity indicators reflect the degree to which an affected resource is integrated into the economic activity of a province. The energy sector assessment takes into account the challenges associated with meeting projected increases in electricity demand, as well as a global imperative to achieve carbon neutrality by the middle of the century. As a universal barometer for measuring adaptive capacity for all three sectors across the provinces, the study uses proxies of their economic and institutional performances. The findings suggest that climate change will likely impact water resources in Central Asia, with varying trends across the provinces. The projections indicate that river discharge may decline in the southern river basins of the region, while it may increase in the northern river basins of the region. During the vegetation season, when water is most needed for irrigation in the southern half, river flow shifts may be more dramatic under both climatic scenarios. Central Asia's strong dependence on water resources is one of the key reasons for its high sensitivity to climate change. This dependence stems from low water productivity, particularly in the southern regions. Transboundary river systems bind downstream countries to the streamflow of upstream countries. Most parts of Turkmenistan, Uzbekistan, and southern Kazakhstan already face water stress, thus any further gap between water availability and demand would exacerbate water scarcity. The countries should prioritize increasing water use efficiency across the sectors as a means of reducing their sensitivity to the adverse impacts of climate change. This is especially relevant for agriculture, which is by far the largest water consumer. Given the current high level of economic reliance on water resources, promoting alternative, less water-intensive sectors of the economy could be a promising additional adaptation approach. Apart from being a general requirement in the development context, this imperative would also strengthen the structural resilience of local economies to anticipated water stress. Future variations in water resource availability may have far-reaching effects on other sectors, with agriculture being the main recipient of the respective risks. Climate change will likely have heterogenous impacts on major crops grown in the region, with some crops seeing reduced yields and others may have the potential for an increase in productivity. Nevertheless, even the potential benefits for some of those crop types would be largely inaccessible in the southern part of the region: crop productivity here will be constrained by the projected decline in water for irrigation. Overall, in many provinces the climate impacts will be magnified by the relatively higher importance of agriculture in the local economy, in terms of share of population engaged and contribution of the sector to regional GDP. Diversification of the economy and the consequent decline in the sector's relative socioeconomic importance may become other important adaptation strategies on a macro scale. The higher sensitivity to climate impacts is also determined in some subregions by excessive monocropping patterns, when agriculture in a province is dominated by one or a few crops that have either negative prospects under climate change or are water-intensive. Reducing reliance on monocropping and crop structure optimization could diminish the sensitivity of the local agricultural sector to climate change. This needs to be complemented with careful selection and alignment of crop varieties to the changing local climate conditions. The drought-resistance of crop cultivars may become one of the important criteria in cropping decisions. The transboundary nature of water resources distribution across Central Asia predisposes the countries to a high degree of interdependence and sensitivity to compound risks, when climate-related impacts on water resources transfer the risks to other sectors. Transboundary linkages are particularly strong in south of the region, where the majority of river runoff originates in the highlands of Tajikistan and Kyrgyzstan, while the majority of withdrawals occur in irrigated farmland in downstream Turkmenistan, Uzbekistan, and south Kazakhstan. While the regional coordination of transboundary water management reduces seasonal and annual water supply uncertainty for downstream provinces, it also reduces their sensitivities and increases overall capacity in the region to adapt to long-term changes in water availability. All countries in the region face a common challenge of maintaining a long-term balance of power demand and supply, given that power consumption is expected to grow by more than half of present generation levels by the middle of the century. The Paris agreement puts an additional burden of GHG emissions reduction, particularly on Kazakhstan, Turkmenistan, and Uzbekistan, where power generation is far more carbon-intensive. This race for power security is compounded in the majority of countries by the high-energy intensity of GDP. While the southern areas of the region are more sensitive to long-term mismatches in power supply–demand, the findings show that many provinces in Kazakhstan are equally vulnerable. High energy and carbon intensity of the Central Asian economies therefore poses risks to long-term electric power security. Improving the economic efficiency of energy use appears to be a cost-effective first step. Many provinces in the region should also prioritize development of less energy-hungry economic sectors. Nonetheless, albeit costly one, large-scale adoption of renewable energy sources appears to be an unavoidable necessity. Long-term electric power security of the countries could also substantially benefit from multiple advantages emerging from regional cooperation, in terms of the lower economic cost of electricity and a greater flexibility to curb GHG emissions. As exemplified, cooperation improves the diversity of power supplies on a regional scale, which is another important element of energy security. It could also establish favorable conditions for exploiting the yet untapped potential of renewable sources in the region, which includes the large hydropower potential in the south. The study used GNI per capita and the government effectiveness (GE) index as proxies for adaptation capacity across Central Asian countries and provinces. Because of the high costs associated with both the adaptation to and mitigation of climate change, lower-income provinces in the region will bear a disproportionate share of the economic burden. Therefore, international development finance will be necessary to strengthen the climate resilience of the Central Asian states. However, resource mobilization alone is unlikely to be sufficient for adaptation. Both the central and local governments should continue to build their capacity in designing and implementing sound sectoral policies.